Long-life magnesium-aluminum-carbon ladle wall brick for steel ladle and preparation method of long-life magnesium-aluminum-carbon ladle wall brick
By using magnesium-aluminum alkaline waste bricks and magnesium carbon brick waste bricks and adding CeSi2-SiC composite materials, the problems of high production cost and environmental pollution of ladle wall bricks are solved, the oxidation resistance and thermal shock stability are improved, and the stability of the thermal shock is extended. service life.
Patent Information
- Application Number
- CN202411449986.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-10
AI Technical Summary
The existing ladle wall tiles have high production costs and short service life, and the production process is highly polluted to the environment, and do not have high thermal shock stability and anti-shrink performance.
Magnesium-aluminum carbon brick waste bricks and magnesium-aluminum carbon brick waste bricks are used as the main raw materials, and CeSi2-SiC composite material is added to the raw materials to prepare long-life laminated magnesium-aluminum carbon wall-clad bricks through mixing and heat treatment to reduce electromelting magnesium sand The use of white corundum improves oxidation resistance and corrosion resistance.
It reduces raw material costs and environmental pollution, improves the comprehensive performance of ladle magnesium-aluminum-carbon wall-clad bricks, including oxidation resistance, corrosion resistance and thermal shock stability, and extends service life.
Smart Images

Figure BDA0005088811720000131 
Figure BDA0005088811720000141 
Figure BDA0005088811720000151
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a long-life steel-clad magnesium-aluminum-carbon clad brick and a preparation method thereof. Background Art
[0002] With the structural adjustment of steel enterprises, high-quality steel varieties have become the leading products of large enterprises. For example, the proportion of high-quality alloy steel, ultra-low carbon steel, clean steel, high-strength steel and other steel types has increased year by year. This has put forward higher requirements on the refractory materials of the ladle wall for smelting. Not only is a longer service life required, but also less pollution and no pollution to the molten steel, and it is best to play a certain purification role.
[0003] At present, domestic ladle wall bricks are mainly magnesium aluminum carbon, aluminum magnesium carbon and magnesium carbon. In order to improve the thermal shock stability of the ladle, the raw materials are often fused magnesia, corundum, graphite and the like as the main raw materials, with phenolic resin as a binder, and pressed into shape by a large-tonnage press. For example, the Chinese patent document with publication number CN111205098A discloses a high-aluminum ladle wall brick and its preparation method, which includes the following raw materials by mass percentage: calcium aluminate titanate 78%, aluminum magnesium spinel 10%, graphite 7%, phenolic resin 3%, aluminum powder 2%, wherein the content of Al2O3 in calcium aluminate titanate is greater than or equal to 80%, the content of Al2O3 in aluminum magnesium spinel is greater than or equal to 60%, and the C content in graphite is greater than or equal to 95%. The invention uses the waste slag left over from alloy production - calcium aluminate titanate as aggregate to replace the original traditional corundum series refractory raw materials. The high-aluminum ladle wall brick produced with this raw material not only reduces the cost but also opens up the market for the reuse of industrial waste slag.
[0004] The raw materials for preparing ladle wall bricks usually use fused magnesia, corundum and other raw materials as the main raw materials. The acquisition of these raw materials requires high-temperature firing, and the high-temperature firing process not only causes great pollution to the environment, but also significantly increases the cost of raw materials. Using magnesium-aluminum-carbon, aluminum-magnesium-carbon and magnesium-carbon waste bricks as raw materials can avoid the firing process when obtaining raw materials and can significantly reduce the cost of raw materials. However, using waste bricks as raw materials will inevitably lead to a decrease in the oxidation resistance, steel erosion resistance, thermal shock stability and other properties of ladle wall bricks.
[0005] Therefore, there is a need for a steel-clad wall brick with low raw material production cost, long service life, low environmental pollution during the production process, and high thermal shock stability and anti-scouring performance. Summary of the invention
[0006] The technical problem solved by the present invention is to provide a long-life ladle magnesium aluminum carbon clad wall brick and a preparation method thereof, aiming to solve the problems of high production cost of the raw materials of the ladle wall brick, short service life, large environmental pollution during the production process, and lack of high thermal shock stability and anti-scouring performance.
[0007] In order to solve the above problems, the first aspect of the present invention provides a long-life steel-clad magnesium-aluminum-carbon clad brick, comprising the following raw materials in percentage by mass:
[0008] Waste magnesia-alumina-carbon bricks 29%-63%, waste magnesia-carbon bricks 10%-20%, fused magnesia 10%-25%, white corundum 2%-5%, α-alumina micropowder 3%-5%, liquid phenolic resin 3%, fused magnesia dust removal powder 1-3%, CeSi2-SiC composite material 0.1%-3%, high-temperature asphalt 1%-3%, graphite 1%-5%.
[0009] Preferably, the raw materials include the following mass percentages: 42%-60% magnesia-alumina-carbon brick waste bricks, 12%-17% magnesia-carbon brick waste bricks, 15%-20% fused magnesia, 2%-3% white corundum, 4%-5% α-alumina micropowder, 3% liquid phenolic resin, 1-3% fused magnesia dust removal powder, 0.1%-1% CeSi2-SiC composite material, 1%-3% high-temperature asphalt, and 1%-3% graphite.
[0010] Preferably, the raw materials include the following mass percentages: 52% waste magnesia-alumina-carbon bricks, 15% waste magnesia-carbon bricks, 19% fused magnesia, 2% white corundum, 5% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 1% CeSi2-SiC composite material.
[0011] Preferably, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 65%-85%, and the volume fraction of SiC is 15%-35%; the carbon content of the high-temperature asphalt is ≥45%; and the carbon content of the graphite is ≥95%.
[0012] Preferably, the particle size of the magnesium-aluminum-carbon brick waste bricks includes magnesium-aluminum-carbon brick waste bricks with a particle size of 5-3mm and magnesium-aluminum-carbon brick waste bricks with a particle size of 3-1mm, and the mass ratio of magnesium-aluminum-carbon brick waste bricks with a particle size of 5-3mm and magnesium-aluminum-carbon brick waste bricks with a particle size of 3-1mm is 1:1.2-1.8; the MgO+Al2O3+C content in the magnesium-aluminum-carbon brick waste bricks is ≥90wt%.
[0013] Preferably, the particle size of the magnesia carbon brick waste bricks includes magnesia carbon brick waste bricks with a particle size of 1-0.5mm and magnesia carbon brick waste bricks with a particle size of 0.5-0mm, and the mass ratio of magnesia carbon brick waste bricks with a particle size of 1-0.5mm and magnesia carbon brick waste bricks with a particle size of 0.5-0mm is 1:1-1.4; the MgO+C content in the magnesia carbon brick waste bricks is ≥84wt%.
[0014] Preferably, the fused magnesia sand particle size includes magnesia carbon brick waste bricks with a particle size of 1-0mm and magnesia carbon brick waste bricks with a particle size of 0-0.074mm, and the mass ratio of magnesia carbon brick waste bricks with a particle size of 1-0mm and magnesia carbon brick waste bricks with a particle size of 0-0.074mm is 1:1-1.4; the magnesium oxide content in the fused magnesia sand is ≥95wt%.
[0015] The second aspect of the present invention provides a method for preparing the above-mentioned long-life steel-clad magnesium-aluminum-carbon clad brick, comprising the following steps:
[0016] The prepared raw materials are mixed to obtain a mixture, and then the mixture is placed in a mold for molding, and then heat treated to obtain the long-life steel-clad magnesium-aluminum-carbon clad wall brick.
[0017] Preferably, S1: first mix waste magnesia-alumina-carbon bricks, waste magnesia-carbon bricks, and fused magnesia, then add liquid phenolic resin to mix, and then add graphite to mix to obtain a mixture; S2: mix and grind fused magnesia, white corundum, α-alumina micropowder, fused magnesia dust removal powder, CeSi2-SiC composite material, and high-temperature asphalt to obtain fine powder; S3: add the fine powder to the mixture, then put it into a mold to form, and then after heat treatment, obtain the long-life steel-clad magnesia-alumina-carbon clad brick.
[0018] Preferably, in step S3, the mixture is molded by a brick press, which is a 630T or 1000T electric screw brick press; the molded product is heat treated by a heat treatment kiln, the temperature inside the heat treatment kiln is 160-240°C during the heat treatment, and the heat treatment time is 12-32h.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The long-life ladle magnesium aluminum carbon clad brick of the present invention uses magnesium aluminum carbon brick waste bricks and magnesium carbon brick waste bricks as main raw materials, reducing the use of raw materials such as fused magnesia sand and white corundum, thereby reducing the environmental pollution and cost increase caused by high-temperature sintering of the raw materials; since the addition of waste brick raw materials will reduce the comprehensive performance of the ladle magnesium aluminum carbon clad brick, the present invention further adds CeSi2-SiC composite material to the raw materials, and the CeSi2-SiC composite material is a multiphase structure composed of CeSi2 phase and SiC phase. In the composite material, CeSi2 reacts with O2 at high temperature to generate CeO2. On the one hand, CeSi2 can be used as an antioxidant and is oxidized before carbon, thereby improving the oxidation resistance of the brick. On the other hand, the generated CeO2 has similar properties to MgO and can be dissolved in the periclase crystal, causing the MgO lattice to distort, promoting the normal development and growth of the periclase crystal, and facilitating the sintering of the material, thereby improving the corrosion resistance of the magnesium-aluminum-carbon brick. In addition, rare earth oxides have high melting points, high chemical activity, and good corrosion resistance. . The SiC phase in the composite material can significantly improve the oxidation resistance of the CeSi2 material. At high temperatures, SiC can form a layer of adherent silicate glass phase on the surface of the CeSi2 material, which can effectively inhibit the further diffusion of oxygen in the CeSi2 material or the interior of the brick. In addition, CeO2 can also react with CaO and SiO2 in the slag to generate high melting point compounds, forming a thin slag permeation layer, which can control the further penetration of the slag. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] The first aspect of the embodiment of the present invention provides a long-life steel-clad magnesium-aluminum-carbon clad brick, comprising the following raw materials in percentage by mass:
[0023] Waste magnesia-alumina-carbon bricks 29%-63%, waste magnesia-carbon bricks 10%-20%, fused magnesia 10%-25%, white corundum 2%-5%, α-alumina micropowder 3%-5%, liquid phenolic resin 3%, fused magnesia dust removal powder 1-3%, CeSi2-SiC composite material 0.1%-3%, high-temperature asphalt 1%-3%, graphite 1%-5%.
[0024] The long-life ladle magnesium aluminum carbon clad bricks of the embodiment of the present invention use magnesium aluminum carbon brick waste bricks and magnesium carbon brick waste bricks as the main raw materials, reducing the use of raw materials such as fused magnesia sand and white corundum, thereby reducing the environmental pollution and cost increase caused by the need to sinter the raw materials at high temperature; due to the addition of waste brick raw materials, the comprehensive performance of the ladle magnesium aluminum carbon clad bricks will be reduced. The present invention further adds CeSi2-SiC composite material to the raw materials. The CeSi2-SiC composite material is a multiphase structure composed of a composite of CeSi2 phase and SiC phase. In the composite material, CeSi2 reacts with O2 at high temperature to generate CeO2. On the one hand, CeSi2 can be used as an antioxidant and is oxidized before carbon, thereby improving the oxidation resistance of the brick. On the other hand, the generated CeO2 has similar properties to MgO and can be dissolved in the periclase crystal, causing the MgO lattice to distort, promoting the normal development and growth of the periclase crystal, and facilitating the sintering of the material, thereby improving the corrosion resistance of the magnesium-aluminum-carbon brick. In addition, the rare earth oxide has a high melting point and high chemical activity, and has good corrosion resistance. The SiC phase in the composite material can significantly improve the oxidation resistance of the CeSi2 material. At high temperatures, SiC can form a layer of adherent silicate glass phase on the surface of the CeSi2 material, which can effectively inhibit the further diffusion of oxygen in the CeSi2 material or the interior of the brick. In addition, CeO2 can also react with CaO and SiO2 in the slag to generate high melting point compounds, forming a thin slag permeation layer, which can control the further penetration of the slag.
[0025] In some embodiments, preferably, the raw materials are included in the following mass percentages: 42%-60% magnesia-alumina-carbon brick waste bricks, 12%-17% magnesia-carbon brick waste bricks, 15%-20% fused magnesia, 2%-3% white corundum, 4%-5% α-alumina micropowder, 3% liquid phenolic resin, 1-3% fused magnesia dust removal powder, 0.1%-1% CeSi2-SiC composite material, 1%-3% high-temperature asphalt, and 1%-3% graphite.
[0026] In some embodiments, the raw materials include the following mass percentages: 52% waste magnesia-alumina-carbon bricks, 15% waste magnesia-carbon bricks, 19% fused magnesia, 2% white corundum, 5% α-alumina micropowder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 1% CeSi2-SiC composite material.
[0027] In some embodiments, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 65%-85%, and the volume fraction of SiC is 15%-35%; the carbon content of the high-temperature asphalt is ≥45%; and the carbon content of the graphite is ≥95%.
[0028] In some embodiments, the particle size of the magnesium-aluminum-carbon brick waste bricks includes magnesium-aluminum-carbon brick waste bricks with a particle size of 5-3mm and magnesium-aluminum-carbon brick waste bricks with a particle size of 3-1mm, and the mass ratio of the magnesium-aluminum-carbon brick waste bricks with a particle size of 5-3mm and the magnesium-aluminum-carbon brick waste bricks with a particle size of 3-1mm is 1:1.2-1.8; the MgO+Al2O3+C content in the magnesium-aluminum-carbon brick waste bricks is ≥90wt%.
[0029] In some embodiments, the particle size of the magnesia carbon brick waste bricks includes magnesia carbon brick waste bricks with a particle size of 1-0.5mm and magnesia carbon brick waste bricks with a particle size of 0.5-0mm, and the mass ratio of magnesia carbon brick waste bricks with a particle size of 1-0.5mm and magnesia carbon brick waste bricks with a particle size of 0.5-0mm is 1:1-1.4; the MgO+C content in the magnesia carbon brick waste bricks is ≥84wt%.
[0030] In some embodiments, the fused magnesia sand comprises magnesia carbon brick waste bricks with a particle size of 1-0 mm and magnesia carbon brick waste bricks with a particle size of 0-0.074 mm, and the mass ratio of magnesia carbon brick waste bricks with a particle size of 1-0 mm and magnesia carbon brick waste bricks with a particle size of 0-0.074 mm is 1:1-1.4; the magnesium oxide content in the fused magnesia sand is ≥95wt%.
[0031] The ratio of CeSi2 to SiC in the CeSi2-SiC composite material will significantly affect the anti-oxidation, slag erosion resistance, thermal shock stability and other properties of the magnesium-aluminum-carbon clad brick. In some embodiments, preferably, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 65%-85%, and the volume fraction of SiC is 15%-35%. When the volume fraction within the above numerical range is used, the magnesium-aluminum-carbon clad brick can have better comprehensive performance.
[0032] A second aspect of an embodiment of the present invention provides a method for preparing the above-mentioned long-life steel-clad magnesium-aluminum-carbon clad brick, comprising the following steps:
[0033] The prepared raw materials are mixed to obtain a mixture, and then the mixture is placed in a mold for molding, and then heat treated to obtain the long-life steel-clad magnesium-aluminum-carbon clad wall brick.
[0034] In some embodiments, S1: first mix waste magnesia-alumina-carbon bricks, waste magnesia-carbon bricks, and fused magnesia, then add liquid phenolic resin to mix, and then add graphite to mix to obtain a mixture; S2: mix and grind fused magnesia, white corundum, α-alumina micropowder, fused magnesia dust removal powder, CeSi2-SiC composite material, and high-temperature asphalt to obtain fine powder; S3: add the fine powder to the mixture, then put it into a mold to form, and then after heat treatment, obtain the long-life steel-clad magnesia-alumina-carbon clad brick.
[0035] In some embodiments, in step S3, the mixture is molded by a brick press, and the brick press is a 630T or 1000T electric screw brick press; the molded product is heat treated by a heat treatment kiln, and the temperature inside the heat treatment kiln is 160-240°C during the heat treatment, and the heat treatment time is 12-32h.
[0036] In the following embodiments, the CeSi2-SiC composite material is prepared by powder metallurgy, and the preparation steps are as follows:
[0037] 1. Powder preparation: Mix silicon carbide powder and cerium disilicide powder in the required proportion;
[0038] 2. Mixing: Use a ball mill or high-energy stirring mixer to evenly mix the two powders;
[0039] 3. Molding: The mixed powder is pressed into a green body of the desired shape by a tablet press;
[0040] 4. Sintering: Place the green body in a high temperature furnace for sintering; usually sintering is carried out at a temperature of 1500-2000°C under the protection of inert gas;
[0041] 5. Annealing: In order to further improve the density and performance of the material, appropriate annealing treatment can be carried out after sintering to obtain CeSi2-SiC composite material.
[0042] Example 1
[0043] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0044] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 5% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 65%, and the volume fraction of SiC is 35%.
[0045] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick in this example comprises the following steps:
[0046] S1: First, mix the waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, the waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, the waste magnesia-carbon bricks with a particle size of 1-0.5mm, the waste magnesia-carbon bricks with a particle size of 0.5-0mm, and the fused magnesia sand with a particle size of 1-0mm; then add the liquid phenolic resin, and finally add the graphite to obtain a mixture;
[0047] S2: fused magnesia with a particle size of 0.074 mm, white corundum with a particle size of 0.074 mm, α-alumina micropowder, fused magnesia dust removal powder, CeSi2-SiC composite material, and high-temperature asphalt are mixed and ground to obtain fine powder;
[0048] S3: adding the fine powder into the mixture, and then putting it into a mold for forming; and then after heat treatment, obtaining the long-life steel-clad magnesium-aluminum-carbon-clad wall brick.
[0049] Example 2
[0050] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0051] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12% fused magnesia with a particle size of 1-0mm, 2.5% white corundum with a particle size of 0.074mm, 5% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 0.5% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 70%, and the volume fraction of SiC is 30%.
[0052] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0053] Example 3
[0054] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0055] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12.9% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 5% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 0.1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 75%, and the volume fraction of SiC is 25%.
[0056] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0057] Example 4
[0058] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0059] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12% fused magnesia with a particle size of 1-0mm, 3% white corundum with a particle size of 0.074mm, 4.5% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 0.5% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 78%, and the volume fraction of SiC is 22%.
[0060] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0061] Example 5
[0062] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0063] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 4% α-alumina powder, 3% liquid phenolic resin, 3% fused magnesia dust removal powder, 1% high-temperature asphalt, and 1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 68%, and the volume fraction of SiC is 32%.
[0064] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0065] Example 6
[0066] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0067] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 4.9% α-alumina powder, 3% liquid phenolic resin, 3% fused magnesia dust removal powder, 1% high-temperature asphalt, and 0.1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 75%, and the volume fraction of SiC is 25%.
[0068] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0069] Example 7
[0070] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0071] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12% fused magnesia with a particle size of 1-0mm, 3.4% white corundum with a particle size of 0.074mm, 5% α-alumina powder, 3% liquid phenolic resin, 1.5% fused magnesia dust removal powder, 1% high-temperature asphalt, and 0.1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 80%, and the volume fraction of SiC is 20%.
[0072] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0073] Example 8
[0074] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0075] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 5% α-alumina powder, 3% liquid phenolic resin, 3% fused magnesia dust removal powder, 0.5% high-temperature asphalt, and 0.5% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 85%, and the volume fraction of SiC is 15%.
[0076] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0077] Example 9
[0078] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0079] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 23% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 8% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 12% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 12% fused magnesia with a particle size of 1-0mm, 13% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 4% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 0.1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 65%, and the volume fraction of SiC is 35%.
[0080] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0081] Example 10
[0082] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0083] 30% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 33% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 4% fused magnesia with a particle size of 1-0mm, 8% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 3% α-alumina powder, 3% liquid phenolic resin, 1% fused magnesia dust removal powder, 1% high-temperature asphalt, and 0.1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 65%, and the volume fraction of SiC is 35%.
[0084] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0085] Embodiment 11
[0086] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0087] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 33% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 7% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 10% fused magnesia with a particle size of 1-0mm, 10% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 3% α-alumina powder, 3% liquid phenolic resin, 1.5% fused magnesia dust removal powder, 1% high-temperature asphalt, and 0.1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 65%, and the volume fraction of SiC is 35%.
[0088] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0089] Example 12
[0090] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0091] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 40% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 2% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 5% fused magnesia with a particle size of 1-0mm, 10% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 4% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 65%, and the volume fraction of SiC is 35%.
[0092] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0093] Embodiment 13
[0094] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0095] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 9% fused magnesia with a particle size of 1-0mm, 10% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 5% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 65%, and the volume fraction of SiC is 35%.
[0096] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0097] Embodiment 14
[0098] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0099] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 5% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 85%, and the volume fraction of SiC is 15%.
[0100] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0101] Embodiment 15
[0102] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0103] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 5% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 70%, and the volume fraction of SiC is 30%.
[0104] Example 16
[0105] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0106] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 5% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 60%, and the volume fraction of SiC is 40%.
[0107] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0108] Embodiment 17
[0109] The long-life steel-clad magnesium-aluminum-carbon clad brick of this embodiment includes the following raw materials in percentage by mass:
[0110] 20% waste magnesia-alumina-carbon bricks with a particle size of 5-3mm, 32% waste magnesia-alumina-carbon bricks with a particle size of 3-1mm, 5% waste magnesia-carbon bricks with a particle size of 1-0.5mm, 10% waste magnesia-carbon bricks with a particle size of 0.5-0mm, 8% fused magnesia with a particle size of 1-0mm, 12% fused magnesia with a particle size of 1-0mm, 2% white corundum with a particle size of 0.074mm, 5% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 1% CeSi2-SiC composite material; wherein, the volume fraction of CeSi2 in the CeSi2-SiC composite material is 50%, and the volume fraction of SiC is 50%.
[0111] The preparation method of a long-life steel-clad magnesium-aluminum-carbon clad brick described in this example is the same as that in Example 1.
[0112] Comparative Example 1
[0113] The difference between this comparative example and Example 13 is that CeSi2-SiC composite material is not added, and the other components and mass percentages remain unchanged.
[0114] The physical and chemical properties and thermal shock resistance of the long-life steel ladle magnesium aluminum carbon clad wall brick obtained in the above embodiments and comparative examples were tested, and the thermal shock resistance was in accordance with the testing standard: GB / T30873-2014, water quenching method. The test results are shown in Table 1 below. It can be seen from the test results that the long-life steel ladle magnesium aluminum carbon clad wall brick of the present application has significantly higher compressive strength and significantly stronger thermal shock resistance than the existing product of Comparative Example 1.
[0115] Table 1 Physical and chemical indicators and thermal shock resistance test of a long-life steel-clad magnesium-aluminum-carbon clad brick
[0116]
[0117]
[0118]
[0119] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A long-life steel-clad magnesium-aluminum-carbon clad brick, characterized in that: The following raw materials are included in mass percentage: Waste magnesia-alumina-carbon bricks 29%-63%, waste magnesia-carbon bricks 10%-20%, fused magnesia 10%-25%, white corundum 2%-5%, α-alumina micropowder 3%-5%, liquid phenolic resin 3%, fused magnesia dust removal powder 1-3%, CeSi2-SiC composite material 0.1%-3%, high-temperature asphalt 1%-3%, graphite 1%-5%.
2. The long-life steel-clad magnesium-aluminum-carbon clad brick according to claim 1 is characterized in that: The following raw materials are included in mass percentage: Waste magnesia-alumina-carbon bricks 42%-60%, waste magnesia-carbon bricks 12%-17%, fused magnesia 15%-20%, white corundum 2%-3%, α-alumina micropowder 4%-5%, liquid phenolic resin 3%, fused magnesia dust removal powder 1-3%, CeSi2-SiC composite material 0.1%-1%, high-temperature asphalt 1%-3%, graphite 1%-3%.
3. The long-life steel-clad magnesium-aluminum-carbon clad brick according to claim 1 is characterized in that: The following raw materials are included in mass percentage: 52% waste magnesia-alumina-carbon bricks, 15% waste magnesia-carbon bricks, 19% fused magnesia, 2% white corundum, 5% α-alumina powder, 3% liquid phenolic resin, 2% fused magnesia dust removal powder, 1% high-temperature asphalt, and 1% CeSi2-SiC composite material.
4. The long-life steel-clad magnesium-aluminum-carbon clad brick according to claim 1 is characterized in that: The volume fraction of CeSi2 in the CeSi2-SiC composite material is 65%-85%, and the volume fraction of SiC is 15%-35%; The carbon content of the high-temperature asphalt is ≥45%; the carbon content of the graphite is ≥95%.
5. The long-life steel-clad magnesium-aluminum-carbon clad brick according to claim 1 is characterized in that: The particle size of the waste magnesium-aluminum-carbon bricks includes waste magnesium-aluminum-carbon bricks with a particle size of 5-3mm and waste magnesium-aluminum-carbon bricks with a particle size of 3-1mm. The mass ratio of the waste magnesium-aluminum-carbon bricks with a particle size of 5-3mm and the waste magnesium-aluminum-carbon bricks with a particle size of 3-1mm is 1:1.2-1.8; the content of MgO+Al2O3+C in the waste magnesium-aluminum-carbon bricks is ≥90wt%.
6. The long-life steel-clad magnesium-aluminum-carbon clad brick according to claim 1 is characterized in that: The particle size of the waste magnesia carbon bricks includes waste magnesia carbon bricks with a particle size of 1-0.5mm and waste magnesia carbon bricks with a particle size of 0.5-0mm, and the mass ratio of the waste magnesia carbon bricks with a particle size of 1-0.5mm and the waste magnesia carbon bricks with a particle size of 0.5-0mm is 1:1-1.4; the MgO+C content in the waste magnesia carbon bricks is ≥84wt%.
7. The long-life steel-clad magnesium-aluminum-carbon clad brick according to claim 1 is characterized in that: The fused magnesia sand particle size includes magnesia carbon brick waste bricks with a particle size of 1-0mm and magnesia carbon brick waste bricks with a particle size of 0-0.074mm, and the mass ratio of magnesia carbon brick waste bricks with a particle size of 1-0mm and magnesia carbon brick waste bricks with a particle size of 0-0.074mm is 1:1-1.4; the magnesia content in the fused magnesia sand is ≥95wt%.
8. A method for preparing a long-life steel-clad magnesium-aluminum-carbon clad brick according to any one of claims 1 to 7, characterized in that: The steps include: The prepared raw materials are mixed to obtain a mixture, and then the mixture is placed in a mold for molding, and then heat treated to obtain the long-life steel-clad magnesium-aluminum-carbon clad wall brick.
9. The method for preparing the long-life steel-clad magnesium-aluminum-carbon clad brick according to claim 8, characterized in that: The specific steps include: S1: firstly mixing waste magnesia-alumina-carbon bricks, waste magnesia-carbon bricks and fused magnesia sand, then adding liquid phenolic resin to mix, and then adding graphite to mix to obtain a mixture; S2: fused magnesia, white corundum, α-alumina powder, fused magnesia dust removal powder, CeSi2-SiC composite material, and high-temperature asphalt are mixed and ground to obtain fine powder; S3: adding the fine powder into the mixture, and then putting it into a mold for molding, and then heat treating to obtain the long-life steel-clad magnesium-aluminum-carbon clad brick.
10. The method for preparing the long-life steel-clad magnesium-aluminum-carbon clad brick according to claim 9, characterized in that: In the step S3, the mixture is molded by a brick press, which is a 630T or 1000T electric screw brick press; the molded product is heat treated in a heat treatment kiln, the temperature inside the heat treatment kiln is 160-240°C, and the heat treatment time is 12-32h.
Citation Information
Patent Citations
High-alumina ladle wall brick for steel ladle and preparation method thereof
CN111205098A
Ultralow-carbon magnesia carbon brick with excellent oxidation resistance and stripping resistance and for steel ladle lining, and preparation method thereof
CN111732416A
Cited By
Magnesium-aluminum-carbon brick with long service life and low cost and preparation method thereof
CN121270221A